2022
DOI: 10.1186/s13731-022-00226-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors impacting university–industry collaboration in European countries

Abstract: This paper aims to examine the links between university-industry collaboration (UIC) predictors (inputs) and the results of UIC cooperation (outputs). The focus of the research is UIC within the European Union member states and the Western Balkan countries. The analysis was conducted using the partial least squares structural equation modeling (PLS-SEM). This method enabled examining the links between variables that are not directly observable. The authors used data for the period of three years, 2015–2018. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Compared to other studies (López-Martínez et al, 2007;Boardman and Ponomariov, 2009;Giuliani et al, 2010;Morales, 2019;Cudic et al, 2021;Da Silva and Sartori, 2022), only López-Martínez et al (2007) and Morales (2019) applied instruments similar to the EA-COOPTEC to measure UIC from the researchers' perspective. However, López-Martínez et al (2007) reported no evidence of validity or reliability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared to other studies (López-Martínez et al, 2007;Boardman and Ponomariov, 2009;Giuliani et al, 2010;Morales, 2019;Cudic et al, 2021;Da Silva and Sartori, 2022), only López-Martínez et al (2007) and Morales (2019) applied instruments similar to the EA-COOPTEC to measure UIC from the researchers' perspective. However, López-Martínez et al (2007) reported no evidence of validity or reliability.…”
Section: Discussionmentioning
confidence: 99%
“…1; (b) expand the sample to be representative by age strata and other variables of interest so that the results can be generalized to other states, at the national level, and in other countries in the region with a similar science and technology system; (c) expand the sample of participating female researchers to reduce possible biases when comparing with the male sample; (d) increase, based on the recommendations of UIC specialists and solid theoretical foundations, the number of items of the Regulation and Normality factor so that the construct faithfully represents the reality to be measured; (e) accompany the application of the EA-COOPTEC v0. 1 with the measurement of other variables in order to provide evidence of concurrent, discriminant and predictive validity, especially those variables associated with institutional factors, human factors, linkage factors, framework factors, intangible product indicators and tangible product indicators (Cudic et al, 2021); and (f) Conduct a study based on the Bayesian Mindsponge Framework (BMF) to consolidate the conceptualization, construction and fit the theoretical model underlying EA-COOPTEC v0. 1 and improve estimation with small sample sizes used for the study of UIC in science and technology systems worldwide (Nguyen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…UIC inputs for these activities are further classified into tangible resources including financial resources and physical resources, and intangible resources (e.g. intellectual property, brand and culture), human-related resources and collaboration capabilities ( Cudi c et al, 2022;Galan-Muros and Davey, 2017;Philbin, 2012). Results from UIC consist of outputs (i.e.…”
Section: The Integrated Conceptual Framework For University-industry ...mentioning
confidence: 99%